Overlapping Investment Permits and Customary Territories: A Legal Analysis of Agrarian Conflict - Anis Noviya (Journal of Adat Recht, 2026)
Agrarian conflicts stemming from overlapping investment permits in customary areas indicate a fundamental problem within the Indonesian legal system, particularly regarding the disharmony between the recognition of customary rights and sectoral licensing policies. This study aims to analyze the conflicting norms between the recognition of customary communities and the granting of investment permits, and to formulate an ideal legal framework for resolving this conflict. The research method used is normative legal research with a statutory and conceptual approach, analyzed qualitatively through primary and secondary legal materials. The results show that the provisions regarding customary rights in the constitution and agrarian regulations are still conditional and open to interpretation, while sectoral regulations tend to facilitate licensing without thorough verification of customary land status. This creates vertical and horizontal normative conflicts that have implications for increasing agrarian conflict. Furthermore, government administrative practices prioritize the formal legality of permits over the substantive recognition of customary rights, thus creating legal uncertainty and distributive injustice. Therefore, regulatory harmonization, strengthening the recognition of customary rights, and reformulating the licensing system based on agrarian justice are needed. A progressive legal approach is also important to ensure that the law functions as a means of achieving substantive justice in resolving agrarian conflicts.